Lichen Striatus with Nail Involvement in a 6-Year-Old Boy - Alexander K. C. Leung; Kin Fon Leong; Benjamin Barankin (Hindawi Limited, 2020)
We describe a 6-year-old boy with an asymptomatic linear eruption on the left index finger with mild erythema of the proximal nail fold, nail dystrophy, and subungual hyperkeratosis of the nail. A diagnosis of nail lichen striatus was made. The child was successfully treated with a topical corticosteroid. Because of its rarity, nail lichen striatus is often under-recognized. Physicians should be familiar with the nail involvement in individuals with lichen striatus so that an accurate diagnosis can be made and unnecessary investigations and treatment avoided.